Empowering Communities Through Maggot Management for Livestock Feed and Organic Fertilizer - M Reza Alfikri; Silfia Silfia (Universitas Djuanda, 2025)
Organic waste management presents a significant challenge for many communities, especially in the agricultural and livestock sectors. The increasing amount of organic waste, particularly in urban areas, has led to environmental issues such as landfill overflow, methane emissions, and pollution. As an innovative solution, the use of Black Soldier Fly (BSF) larvae has proven effective in converting organic waste into animal feed and organic fertilizers. This study aims to develop a community-based training program focusing on the utilization of BSF larvae for organic waste management and the production of value-added products. The implementation method includes identifying suitable locations, designing the training program, and providing post-training support to participants. Results show that participants successfully applied BSF farming techniques using local organic waste, producing high-quality animal feed and organic fertilizers that enhanced agricultural productivity. Additionally, this technology reduced feed costs, lessened dependence on chemical fertilizers, and minimized the volume of waste disposed of in landfills. The discussion highlights challenges related to infrastructure and the availability of quality organic waste. The main conclusion of the study is that BSF farming provides a sustainable solution that can improve food security, reduce environmental impacts, and strengthen local economies through community empowerment.